A trans-scalar approach to peacebuilding and transitional justice: Insights from the Democratic Republic of Congo. (December 2022) - Hellmüller, Sara
Peace research has taken a local turn. Yet, conceptual ambiguities, risks of romanticization, and critiques of co-option of the "local" point to the need to look for novel ways to think about the interactions of actors ranging from the global to the local level. Gearoid Millar proposes a trans-scalar approach to peace based on a "consistency of purpose" and a "parity of esteem" for actors across scales. This article analyzes the concept of trans-scalarity in the peace process in Ituri, a province in the northeastern Democratic Republic of Congo (DRC). Drawing on qualitative data from more than a year of research in the DRC, I argue that while a trans-scalar approach was taken to end violence, it was not applied to transitional justice initiatives. The result was a negative, rather than a positive peace. By showing the high, but still untapped, potential of trans-scalarity, the article makes three contributions. First, it advances the debate on the local turn by adding empirical insights on trans-scalarity and further developing the concept's theoretical foundations. Second, it provides novel empirical insights on the transitional justice process in the DRC. Third, it links scholarship on peacebuilding and transitional justice, which have often remained disconnected.